2015
DOI: 10.1017/s1366728915000474
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of bilingualism and public speaking training to cognitive control differences among young adults

Abstract: The Flanker and Number Stroop tasks, and the Wisconsin Card Sorting Test (WCST) were adopted to examine how bilingualism and public speaking training would contribute to cognitive control differences among young adults. Four groups of participants (of similar cultural and language backgrounds) were tested: monolinguals, general bilinguals, L1 public speaking bilinguals, and L2 public speaking bilinguals. Both ANOVA and multiple regression analyses showed that public speaking experience (esp. in L2) significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…Prior and MacWhinney (2010), for example, adopted a Color-Shape switch task to compare monolinguals’ and bilinguals’ switching ability and found that bilinguals incurred smaller switching costs than monolinguals. In a more recent study, Xie and Dong (2017) compared Chinese–English bilinguals and Chinese monolinguals on the WCST and found that bilinguals performed better than monolinguals by completing more categories and making fewer errors. However, in the current study we found no differences between groups that differed in L2 proficiency, although a monolingual group was not included.…”
Section: Discussionmentioning
confidence: 99%
“…Prior and MacWhinney (2010), for example, adopted a Color-Shape switch task to compare monolinguals’ and bilinguals’ switching ability and found that bilinguals incurred smaller switching costs than monolinguals. In a more recent study, Xie and Dong (2017) compared Chinese–English bilinguals and Chinese monolinguals on the WCST and found that bilinguals performed better than monolinguals by completing more categories and making fewer errors. However, in the current study we found no differences between groups that differed in L2 proficiency, although a monolingual group was not included.…”
Section: Discussionmentioning
confidence: 99%
“…The indicator for conflict monitoring is sometimes the RT difference between trials in a pure block and the congruent trials in a block where congruent and incongruent trials are mixed, sometimes RT on the congruent trials, or RT on both the congruent and incongruent trials Costa et al, 2009;Paap and Greenberg, 2013). In the current study, we use the RTs on each condition as the indicator of conflict monitoring (as in Dong and Xie, 2014;Xie and Dong, 2017). In the current flanker task, there were three conditions: congruent, incongruent, and neutral.…”
Section: The Flanker Taskmentioning
confidence: 99%
“…The flanker task, adapted from previous studies (Luk et al, 2010;Xie and Dong, 2017), was computerized via E-prime 2.0. The task was composed of a practice block with feedback (smiling face for correct, frowning face for incorrect) and a formal experimental block without feedback.…”
Section: The Flanker Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…As it can be also consulted in Table 1, monolinguals were younger than bilinguals, and, presumably because of this (r Age, Years of Education = .778, p < .0001), the monolingual group reported a lower number of years of University education. However, it has been argued that age should not be considered important at these developmental periods (early twenties) because both groups are at their executive control prime (Xie & Dong, 2017).…”
Section: Sample and Proceduresmentioning
confidence: 99%